Pibid - Institutional Program of Initiation to Teaching Scholarship contribution to teaching training (Research, Society and Development, 2020)
This reseach aims to understand the contributions of the Pibid Program [in English, Institutional Program of Initiation to Teaching Scholarship] to Initiation to Teaching former scholars in the Pedagogy Course of IFC [Federal Institution Catarinense], in the city of Camboriu. It is a qualitative investigation of analitical-discriptive and interpretative type, with content analysis features. We used the focus group technique for data collection. Seven former scholars of the IFC Pedagogy Course participated in the focus group, through which there was a reflective moment about their experiences along the Program. The Pibid Program contributed in the sense of confronting reductionist and fragmented pedagogical practices along the journey of the former students in the Program, giving place to professional insertion situations, articulations between theory and practice, research practices as an educational and scientific principle, interdisciplinary practices, possibilities of “being a teacher”, improvement of leraning processes of the students inside the field-school, leading to experiences of authorship, autonomy and innovative knowledge production.